(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
When we read that the weather is not in good condition, often our hearts are touched to do something for the Earth, our home. However, it means that we are making the Earth as an object that exists independently of us? This perspective tends to place humans “higher” than non-human entities. Graham Harman dismantles that duality and proposes a way return to its being, asserting that both have an equivalent ontological basis that can no longer be reduced. This thought does not want to show that we are helpless in the face of nature, but we can do some action through aesthetics. This paper will use a fully literature-based method and rotate around the axis of Graham Harman’s thinking, especially the principles of Object-Oriented Ontology (OOO). This new proposition is expected to provide us with a better basis for how we perceive nature